The Consent in Contracting By Electronic Means With A Professional Party According to the New French Law of Contract of 2016-: An Analytical Comparative Study With The Iraqi Law - Younis Salahuddin Ali (Journal of Legal Sciences, 2024)
This research is concerned with studying the consent in contracting by electronic means with any person in general، and with a professional in particular، in the light of the French civil code، amended by the ordinance No.2016-131 dated February 10، 2016 concerning reforms of the law of contract، general regime and proof of obligations. The study is aimed at the benefit of the Iraqi law from the special rules of the new French law of contract as exemplary rules، concerning the expression of the consent in contracting by electronic means، particularly with a professional. The problem of the study lies in how to fill the gaps in both the Iraqi civil law No.40 of 1951، and the law of electronic signature and electronic bargains No.78 of 2012 regarding the up-to-date requirements and modalities of the consent in contracting by electronic means، and its components of the offer and acceptance. To achieve this aim، the study adopts the comparative analytical methodology of legal research. The most significant findings that the study reached are the considerable shortage of the legal regulation and the rules concerning the consent in contracting by electronic means in the Iraqi civil law، as compared to the detailed regulation of this topic in the French law of contract. Finally the study suggested many recommendations to the Iraqi legislator to follow suit the new rules of the French law of contract particularly the article (1127).